Participatory plant breeding in maize for the Chhotanagpur plateau of Eastern India - Kumar, Arun; Ganguli, D.K.; Prasad, S.C.; Gangwar, J.S.; Virk, Daljit S.; Witcombe, John R. (CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation, 2001)
This paper describes a participatory maize breeding program that is a collaborative project between Birs, Agricultural University and the KRlBHCO Indo-British Rain fed Farming Project (East). At the beginning of the project, a base population was produced in Ihe rainy season of 1997 by making nine crosses between three yellow-endospermed flint varieties (Suwan, Birsa Makka, and Chandan) and three white endospermed flint varieties (GDRM 187, Shweta, and Rudarpur local). The parental varieties were selected either because farmers in the project area had accepted them or because they contributed complementary) trails to the population. The population has been randomly mated for five cycles by hilI-planting seed derived from the original nine crosses and detasseling 50% of the plants. After the initial random mating, each cycle was planted from pale yellow grains that should be heterozygous at the locos controlling endosperm color. Three composite varieties have been extracted from cycles three and fount by random mating of early-maturing plants (75 to 80 days) with either yellow or white grains. Preliminary results show that these populations are superior to local checks for multiple traits. lntervarietal hybrids were also made from farmer-preferred varieties. Farmer-managed participatory research (FAMPAR) trials conducted in the rainy season. Of 1998 showed that farmers preferred the BM 1 x Suwan intervarietal hybrid to the local varieties. Further evaluations of hybrids in on-farm and station trials are being conducted.